(untitled) (Journal of the Bangladesh Agricultural University, 2013)
This study was undertaken at Trishal upazila of Mymensingh, Bangladesh to investigate the farmers awareness on environmental degradation nearby the brickfield areas and to explore the relationship between the selected characteristics of the farmers (i.e. independent variables) with their awareness on environmental degradation (i.e. dependent variable). Thirty five farmers were selected randomly from a total of 175 farmers under Amiandangori village of Balipara union and thirty farmers were selected randomly from a total of 150 farmers under Dauaniabari village of Boilor union of Trishal upazila in Mymensingh district. Personal interview schedule was used for collecting data. Simple and direct questions and different scales were used to obtain desired information. Co-efficient of correlation (r) was computed in order to explore the relationships between the dependent and independent variables. The findings revealed that majority (47.70 percent) of the farmers had medium level of awareness on environmental degradation nearby the brickfield areas. Farmers characteristics like academic qualification, farm size, annual income, extension media contact, and knowledge on environmental degradation had significant (p <0.05) positive relationship with their awareness on environmental degradation. Besides, the findings revealed that majority (57 percent) of the respondents expressed their opinion towards medium vulnerability, 15 percent low vulnerability and 28 percent high vulnerability of environmental degradation nearby the brickfield areas. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14716 J. Bangladesh Agril. Univ. 10(2): 229-233, 2012